Dependence of Height, Total Number and Quantity of Productive Stems of Winter Barley Varieties on Different Sowing Date and Mineral Fertilizer Application Rates (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article presents data on the effects of different planting dates and mineral fertilizer application rates on plant height, growth and development, and the number of total and productive stems in winter barley varieties "Ikhtiyor", "Obikor" and "Kizilkurgan".